2004
DOI: 10.1074/jbc.m312300200
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional Regulation by the Repressor of Estrogen Receptor Activity via Recruitment of Histone Deacetylases

Abstract: Histone acetyltransferases and deacetylases are recruited by transcription factors and adapter proteins to regulate specific subsets of target genes. We were interested in identifying interaction partners of histone deacetylase 1 (HDAC1) that might be involved in conferring target or substrate specificity. Using the yeast twohybrid system, we isolated the repressor of estrogen receptor activity (REA) as a novel HDAC1-associated protein. We demonstrated the in vivo interaction of REA with HDAC1 and characterize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
86
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(91 citation statements)
references
References 68 publications
5
86
0
Order By: Relevance
“…Phb2 was found to repress the transcriptional activity of the estrogen receptor in breast cancer cell lines by competing for coactivator binding sites on estrogen receptor in the nucleus (21) (57). Due to this inhibitory action, the protein was named repressor of estrogen receptor activity, however, it has recently been shown to interact with histone deacetylases HDAC1 and HDAC5 to mediate repression of COUP-TFs, suggesting a more general nuclear receptor corepressor function (58). Interestingly, nuclear Phb2 was recently shown to protect sister chromatid cohesion during mitosis in the cervical carcinoma cell line, HeLa (59).…”
Section: Discussionmentioning
confidence: 99%
“…Phb2 was found to repress the transcriptional activity of the estrogen receptor in breast cancer cell lines by competing for coactivator binding sites on estrogen receptor in the nucleus (21) (57). Due to this inhibitory action, the protein was named repressor of estrogen receptor activity, however, it has recently been shown to interact with histone deacetylases HDAC1 and HDAC5 to mediate repression of COUP-TFs, suggesting a more general nuclear receptor corepressor function (58). Interestingly, nuclear Phb2 was recently shown to protect sister chromatid cohesion during mitosis in the cervical carcinoma cell line, HeLa (59).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, in other cell types, PHB2 has also been suggested to be localized in the nucleus and modulate transcriptional activity by interacting with transcription factors, including nuclear receptors, either directly or indirectly 12,[29][30][31][32] . PHB2 has been shown to interact with and inhibit the transcriptional activity of the ER in breast cancer 12 .…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the unexpected maspin/HDAC1 interaction turned out not entirely surprising. Indeed, Kurtev et al (44) recently reported that HDAC1 may bind to chick ovalbumin, a classic noninhibitory serpin homologue of maspin. Interestingly, maspin was not associated with other class I HDACs (e.g., HDAC2 and HDAC3, and data not shown) despite their sequence homologies with HDAC1 (45,46).…”
Section: Discussionmentioning
confidence: 99%